GILL, KIDNEY, INTESTINE, AND LIVER STRUCTURES OF Pangasianodon hypophthalmus REARED UNDER BIOFLOC SYSTEM AND PHOTOPERIOD MANIPULATION - Pardede, Alfred Nobel; Windarti, Windarti; Efawani, Efawani (Asian Journal of Aquatic Sciences, 2022)
Pangasianodon hypophthalmus is a freshwater fish that can grow well in dark condition. In no light condition, fishes are more responsive to feed provided. However, phytoplankton may not grow well, and as a consequence the water quality was poor and it negatively effects the fish health in general. The combination of biofloc and photoperiod manipulation systems is expected to improve the water quality as well as the fish health. To understand health status of the fish in general, the histological structure gill, kidney and liver was investigated. Sample were fixed in 5% formalin, paraffin processed and Haematoxylin Eosin stained. There were 2 factor, 3 treatment applied, namely natural (control), 18G (18 hours dark), 24G (24 hours dark) and 3 repetition. Parameter measured were survival rate and histological structure of gill, kidney, intestine and liver. Results shown that there are not difference of histological structure of the organs of fish reared under biofloc and manipulated photoperiod systems. There were light abnormalities in the gill, such as hyperplasia, hypertrophy, oedema and necrosis. There is no negative effect of biofloc system and photoperiod manipulation in structure of fish organ as there is only light abnormalities that can be cured when the water quality is good.